Molecular Basis for the Enhanced CDK2 Inhibition by Artesunate: Superior Binding Affinity to the ATP-Catalytic Site - Mohammad Rizki Fadhil Pratama; Evi Mulyani; Suratno Suratno; Punet Kumar; Daryono Hadi Tjahjono; Tutus Gusdinar Kartawinata (Universitas Lambung Mangkurat, 2026)
This study aimed to identify the most potent CDK2 inhibitor among seven artemisinin derivatives and, critically, to elucidate its binding mechanism and compare its affinity with that of the natural ligand, ATP. Molecular docking was performed using AutoDock 4.2.6 toward inactive and active forms of CDK2. Ligands were optimized using the Hartree-Fock method basis set 6-311G. Blind docking on the active form was used to determine the inhibition mechanism, employing the free energy of binding (Î”G) and dissociation constant (Ki) as affinity markers. Artesunate was the most potent derivative, exhibiting the highest affinity towards the active CDK2 form, with a Î”G of -11.7 kcal/mol and a Ki of 2.66 nM. Blind docking confirmed an ATP-competitive inhibition mechanism. Remarkably, Artesunate's Ki was significantly lower than that of ATP (8.73 nM). This enhanced affinity is attributed to specific interactions between the hemisuccinate side chain and the critical amino acid region, from 13-Gly to 16-Gly. Artesunate is suggested as a potent, ATP-competitive CDK2 inhibitor with an affinity exceeding that of ATP. These hypothesis-generating results suggest anticancer potential, yet require validation via MD or assays; limitations like scoring bias and protein flexibility necessitate cautious interpretation regarding the 13-Gly to 16-Gly target.